Professionalisation in nursing : the Swiss case - Daetwyler, Barbara (2007)
In this study, the professionalisation of nursing in Switzerland is being investigated with the help of the theoretical approaches of the sociology of professions. These approaches - demand approach and supply approach - represent two opposing lines of argumentation. In the demand approach, the status of being a profession (monopolised autonomy by state licence, social standing) is ascribed to successful political strategies of the professional group. In the supply approach, the professions are seen as institutions which can only be explained in their relationship to the state. Thus, in one line of thought, the constitution of the professions is viewed as a process parallel to the modernisation of the state. Another line of thought understands the professions also as bearers of uncertainty of both individuals and collectives. In the course of global neo-liberal politics, the ethic aspect of this approach has been condensed into the soul of the professions - as an antagonist to the soullessness of state and market.